Factors affecting the shape of MBE-grown laterally aligned Fe nanowires - Lok, Shu K. (2013)
Various microstructural and chemical analysis techniques were applied to study two types (type-A and B) of self-assembled laterally aligned Fe nanowires (NWs) fabricated by molecular beam epitaxy on a ZnS buffer layer. The formation of the three-dimensional shapes of these NWs was found to be driven by the principle of surface energy minimization. We have provided phenomenological models to address the factors affecting the observed topological shape of these NWs, including the role of the lattice relationship between the Fe NWs and the underlying buffer layer, growth temperature, Fe nominal coverage and substrate orientation. Magnetic hysteresis measurements were performed at different temperature, demonstrating the Fe NWs possess a coercivity about 30 times larger than that of a Fe thin film. The observed gradual magnetization reversal indicates the magnetization process is accomplished by the rotation of magnetic moments within a single domain.